The Psychological and Communicative Effects of Colors on Pilgrims Visiting Janam Astana Baba Guru Nanak, Nankana Sahib - Muhammad Abu Bakar; Aslam, Muhammad Zia (ACADEMIA International Journal for Social Sciences, 2025)
Colors are a fundamental aspect of human perception, influencing emotions, attention, and behavior. In the context of religious sites, colors also carry cultural and spiritual significance. This study investigates the effects of colors on pilgrims visiting Janam Astana Baba Guru Nanak in Nankana Sahib. Using a mixed-method approach, surveys were conducted with 75 pilgrims, supplemented by semi-structured interviews and observational analysis of the site’s color usage in walls, signage, and decorations. Findings indicate that certain colors, such as saffron, white, and blue, evoke feelings of calmness, spirituality, and focus, while bright or contrasting colors can distract visitors from contemplative experiences. The study highlights the importance of culturally and psychologically informed color choices in enhancing visitor engagement and communication within sacred spaces.